1997
DOI: 10.1037/0022-006x.65.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in partner violence in a birth cohort of 21-year-olds: Bridging the gap between clinical and epidemiological approaches.

Abstract: This study describes partner violence in a representative sample of young adults. Physical violence perpetration was reported by 37.2% of women and 21.8% of men. Correlates of involvement in severe physical violence differed by gender. Severe physical violence was more strongly associated with unemployment, low educational attainment, few social support resources, polydrug use, antisocial personality disorder symptoms, depression symptoms, and violence toward strangers for men than for women. Women who were vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
367
2
21

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(426 citation statements)
references
References 30 publications
36
367
2
21
Order By: Relevance
“…37 We recognize that these findings have been challenged because the Conflict Tactics Scale 39 does not elicit information about relationship context, motivation of the perpetrator, or potential of injury to the victim. However, others have confirmed female individuals can be aggressive, especially within the context of a relationship, 40,41 using moderately severe forms of aggression as measured by Conflict Tactic Scale items.…”
Section: Discussionmentioning
confidence: 99%
“…37 We recognize that these findings have been challenged because the Conflict Tactics Scale 39 does not elicit information about relationship context, motivation of the perpetrator, or potential of injury to the victim. However, others have confirmed female individuals can be aggressive, especially within the context of a relationship, 40,41 using moderately severe forms of aggression as measured by Conflict Tactic Scale items.…”
Section: Discussionmentioning
confidence: 99%
“…We report data gathered at age 21, when 92% of the living study members provided data about their intimate relationships and mental health. Sample, design, and data are described extensively elsewhere (9,10,11,12).…”
Section: Methodsmentioning
confidence: 99%
“…We report data gathered at age 21, when 92% of the living study members provided data about their intimate relationships and mental health. Sample, design, and data are described extensively elsewhere (9,10,11,12).Partner violence in the previous 12 months was measured using the Conflict Tactics Scales (CTS) (13). We examined Any Physical Violence, which referred to any of three minor or six severe violent behaviours in the CTS (minor: throw object at partner, push/grab/shove partner, slap partner; severe: kick/bite/hit with fist, hit with object, beat up, choke/strangle, threaten with a knife/gun, use a knife/gun) and Severe Physical Violence, which referred to any of the six severe violent behaviours in the CTS.…”
mentioning
confidence: 99%
“…Extremely conflicting results about the prevalence of dating violence have been reported, with one-year prevalence rates ranging from 9 to 37% for young women and 6 to 36% for young men, probably partly because dating violence has not been strictly defined, but also because the questions relating to violence have differed greatly [11,12,15,16,20,21,34,37]. In this study, the prevalence of violence was higher among the young men, but, as has been pointed out earlier, the aftermath appeared to be worse for the young women, with higher odds ratios for most health outcomes and specifically for health care utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional studies have demonstrated mainly mental but also to some extent physical health consequences of intimate partner violence in men as well [10]. However, only a few reports on violence against teenagers and young women and men have been published, apart from studies relating to dating violence, which are *Address correspondence to this author at the Management Staff, Department of Public Health SE-871 85 Härnösand, Sweden; Tel: +46 61180078; E-mail: niclas.olofsson@lvn.se fairly abundant [11][12][13][14][15][16][17][18][19]. There is no strict definition of dating violence, but it is often described as physical violence, sometimes also including emotional or sexual violence, by a boyfriend, dating partner or intimate partner [13,16,18,20].…”
Section: Introductionmentioning
confidence: 99%